Respon Warganet Mengenai Pernikahan Beda Agama - Riesardhy, Anastasia Winanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Indonesia's diversity creates opportunities for interfaith marriages. Although these marriages cannot be legally registered in Indonesia, their prevalence is increasing. This controversy stems from the belief that marriage is a private matter and shouldn't be regulated by the state. This study aims to describe public sentiment towards interfaith marriage through the Cretivox YouTube video